Optimizing the Role of Teachers in the Learning Process with a Modern Pedagogical Approach: Bibliometric Analysis - Harry Hermawan; A Sobandi (Universitas Negeri Padang, 2024)
This research aims to understand the role of optimizing the teacher's role in developing learning in a modern pedagogy approach. The research was conducted through a systematic literature review and bibliometric analysis. Initially, an article search was carried out using the Google Scholar database in the Publish or Perish application with the keywords